2001
DOI: 10.1002/1521-3927(20010301)22:5<376::aid-marc376>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Polycarbonate from Carbon Monoxide and Bisphenol A Using Efficient Pd Complex Catalyst Systems

Abstract: A direct oxidative carbonylation procedure of Bisphenol A to polycarbonate catalyzed with efficient Pd complex systems has been developed. Pd/2,2′‐bipyridyl complexes possessing 6,6′‐dimethyl substituents, Pd/2,2′‐biquinoline complexes, and dinuclear Pd complexes bridged with a pyridylphosphine ligand were found to give higher molecular weights and yields than conventional Pd catalyst systems. Highest molecular weight (M̄n = 5 600, M̄w = 12 900) and yield (86%) were obtained using the Pd/6,6′‐dimethyl‐2,2′‐bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Therefore, a more environmentally favorable technology for PC synthesis must be developed to replace the melt process. Recently, a new PC‐producing technology, a modified solution method, has been attracting interest for the preparation of PCs directly from carbon monoxide and BPA with Pd compound/redox catalyst/onium halide systems 3, 4. A study reported that via oxidative carbonylation, the molecular weight of PCs obtained with these catalyst systems was high, and the highest number‐average molecular weight ( M n ) of the PCs was M n = 9400.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a more environmentally favorable technology for PC synthesis must be developed to replace the melt process. Recently, a new PC‐producing technology, a modified solution method, has been attracting interest for the preparation of PCs directly from carbon monoxide and BPA with Pd compound/redox catalyst/onium halide systems 3, 4. A study reported that via oxidative carbonylation, the molecular weight of PCs obtained with these catalyst systems was high, and the highest number‐average molecular weight ( M n ) of the PCs was M n = 9400.…”
Section: Introductionmentioning
confidence: 99%
“…[269] Ishii and corkers have pioneered the oxidative carbonylation as a very versatile new route to the phosgene and halogen free synthesis of polycarbonates directly from bisphenol or via the diphenylcarbonate monomer. [270][271][272] In addition to the oxidative carbonylation of bisphenol ( Figure 40), also diphenylcarbonate monomer is prepared by oxidative carbonylation and used in a transesterification process to prepare polycarbonate and to recycle the phenol byproducts, again by means of oxidative carbonylation. While the catalytic onestep polycarbonate synthesis is more difficult to perform with respect to formation of high molecular weights, the production of diphenyl carbonate monomer as intermediate is compatible with established phosgene free transesterification processes which use bisphenol A and diphenyl carbonate as monomers.…”
Section: Polar Copolymers and Other Feed Stocksmentioning
confidence: 56%
“…Also, 1b , which is a derivative of 1a with methyl groups at the 6,6′‐position of 2,2′‐bipylidine‐5,5′‐diyl moiety, was examined. According to previous reports,4, 6 when using the homogeneous catalyst, the Pd/6,6′‐dimethyl‐2,2′‐bipyridyl complex is more effective than the Pd/2,2′‐bipyridyl complex that lacks the substituents at the 6,6′‐position. When using the heterogeneous catalyst, however, the substituent effect was not generated while, with the Pd/poly(2,2′‐bipyridyl) complex, PC was produced.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, a more environmentally favorable technology for PC synthesis must be developed other than the melt process. Recently, a new PC producing technology, a modified solution method, has been attracting interest to prepare PC directly from carbon monoxide and BPA using Pd compound/redox catalyst/onium halide systems 3, 4. A study reported that, via oxidative carbonylation, the molecular weight of PC obtained with these catalyst systems was high, and the highest number‐average molecular weight ( M n ) of PC was 9400.…”
Section: Introductionmentioning
confidence: 99%